Corrosion Inhibition of Mild Steel Using Rhodamine-B in Distinct Media - Sahu, G.P.; Lavale, S.C. (Asian Journal of Chemistry, 2016)
The effectiveness of rhodamine-B [RHB] as corrosion inhibitor for mild steel [MS] in distinct media/solution has been studied by weight loss, electrochemical and voltammetric methods. Adsorption of rhodamine-B on mild steel surface obeys Langmuir adsorption isotherm. Percentage inhibition efficiency of rhodamine-B for mild steel in aqueous, acidic and basic media has been calculated by weight loss method. The data revealed that RHB is a very effective inhibitor for MS in acidic media even at extremely low level of concentration 1 × 10-4 mol dm-3. Inhibition efficiency increased with the concentration of RHB and decreased with temperature. Heat of adsorption of rhodamine-B values ranging from 4.2 to 11.6 kcal in the entire range of study signifies that the physical adsorption of the dye occurs over the metal surface. Cathodic and anodic polarization curves of mild steel in presence of different concentrations of RHB at 30 ºC reveal that it is a mixed type of inhibitor with slight predominance over cathodic character. There is a good agreement between inhibitor efficiency values as calculated from weight loss and polarization technique with slight deviation in data computed. Dependence of corrosion behavior of MS on thermodynamic instability, adsorption, time, polarization and temperature is discussed in detail.